The Role of Digital Mindset in Mediating the Relationship between Technological Literacy and the Sustainability of Social Digital Businesses in F&B MSMEs in Pasuruan Regency - Miftahul Huda; Sri Wahyuni (SKeTsa Bisnis (e-jurnal), 2025)
Introduction, this study focuses on the important role of micro, small, and medium enterprises (MSMEs) in Indonesia’s economy, particularly in the food and beverage (F&B) sector in Pasuruan Regency. Although digital marketing adoption continues to grow, many MSMEs still face challenges in achieving digital social business sustainability due to limited technological literacy and a lack of adaptive digital mindsets. Methods, this research uses a quantitative approach with path analysis processed through SPSS. The study examines how Technological Literacy affects Digital Social Business Sustainability, with Digital Mindset acting as a mediating variable among F&B MSMEs in Pasuruan Regency. Results, the findings show that Technological Literacy significantly influences both Digital Mindset (β = 0.215) and Digital Social Business Sustainability (β = 0.386). In addition, Digital Mindset has a significant positive impact on sustainability (β = 0.430). The model explains 76% of the variation in sustainability (R² = 0.76), indicating a strong predictive capability. Conclusion, the study concludes that Digital Mindset partially mediates the relationship between Technological Literacy and Digital Social Business Sustainability. These findings highlight the importance of enhancing both digital skills and adaptive thinking to strengthen MSME competitiveness in the digital era.